Analysis of CI/CD Application in Kubernetes Architecture - K.Janani, K.Anuhya, V.L.Manaswini, V.Likitha, B.Suneetha, T.Vignesh (Mathematical Statistician and Engineering Applications, 2023)
Technology is your innovation engine and delivering your application faster helps you win. Automation ensures high quality results. CI/CD using Jenkins ansible enables higher efficiency and increased productivity. Jenkins help organizations accelerate the software development process through automation. Jenkins integrates development life-cycle processes of all kinds and by using plugins, achieves CI it makes the preferred choice of many DevOps teams. Ansible is a potent tool for automating the deployment of the application and the provisioning of the target environment. It is an open-source tool for service employment and a solution for software provisioning, application deployment and configuration management. Ansible is a potent tool for automating the deployment of the application and the provisioning of the target environment. It saves time. It is more productive, secure and reliable